Personalized intrahepatic cholangiocarcinoma prognosis prediction using radiomics: Application and development trend - Chen, Pengyu; Yang, Zhenwei; Zhang, Haofeng; Huang, Guan; Li, Qingshan; Ning, Peigang; Yu, Haibo (Frontiers in Oncology, 2023)
Radiomics was proposed by Lambin et al. in 2012 and since then there has been an explosion of related research. There has been significant interest in developing high-throughput methods that can automatically extract a large number of quantitative image features from medical images for better diagnostic or predictive performance. There have also been numerous radiomics investigations on intrahepatic cholangiocarcinoma in recent years, but no pertinent review materials are readily available. This work discusses the modeling analysis of radiomics for the prediction of lymph node metastasis, microvascular invasion, and early recurrence of intrahepatic cholangiocarcinoma, as well as the use of deep learning. This paper briefly reviews the current status of radiomics research to provide a reference for future studies.